Ficus exasperata leaves aqueous extract influences pathophysiolgic mechanisms of diabetic peripheral neuropathy in a rat model - Hidaayah Oluwamayowa Jimoh-Abdulghaffaar, Ayodeji Johnson Ajibare, Olabode Oluwadare Akintoye, Olanrewaju Saheed Jimoh, Evelyn Nnashiru Ananias, Joshua Oladiipo Owoyemi, Victor Oluwatoju Ibiyeye, Lekan Sheriff Ojulari (Journal of Applied Pharmaceutical Science, 2023)
Aqueous extract of Ficus exasperata leaves was investigated for its antinociceptive and anti-oxidant activities in streptozocin (STZ)-induced diabetic peripheral neuropathic rats. 36 male albino rats weighing between 120 and 170 g were randomly assigned into four groups of nine animals each. Rats in group 1 (non-diabetic) received normal saline 1.0 ml/kg b.w., group 2 (diabetic untreated) received normal saline 1.0 ml/kg b.w., group 3 were treated with pregabalin 0.71 mg/kg b. w. and group 4 were treated with F. exasperata 200 mg/kg b. w. following the onset of peripheral neuropathy after induction of diabetes, rats received drug treatment orally, once daily for 21 days. They were then sacrificed ad blood, brain, skin, and sciatic nerve samples were collected. The plasma was assayed for glutathione and superoxide dismutase, the brain was assayed for malondialdehyde and nitric oxide, and the skin was assayed for Calcitonin gene-related peptide and Substance P, while the sciatic nerve was assayed for brain-derived neurotrophic factor and nerve growth factor. Pain threshold was assessed by testing for thermal allodynia using ice-cold and hot plate tests. Aqueous leaf extract of F. exasperata reversed hyperglycemia, allodynia, and oxidative stress induced by STZ.